Achieving Environmental Design Characteristics in Contemporary Desert Cities Acomparison Petween the Planning of Streets (Alleys) in the Old and Modern City of Ghadames - Waled Abdulslam Freewan & Abdalsalam Mohamed Alrachidy (Journal of Pure & Applied Sciences, 2019)
In this study, the researchers made on  attempt to compare between traditional and modern planning in the desert Ghadames city , where this study is based on comparison between two models in terms of planning the streets (alleys) in the old and modern city, which represented in (Tokach) district, and in this research proved that modern street planning has not achieved the thermal comfort for it users although trying to quote what is found in the old city, in terms of the shape of streets and buildings, this has done by analytic and standard study, processed for the two models.